2021
DOI: 10.1016/j.jbc.2021.101151
|View full text |Cite
|
Sign up to set email alerts
|

Impact of temperature on the affinity of SARS-CoV-2 Spike glycoprotein for host ACE2

Abstract: The seasonal nature of outbreaks of respiratory viral infections with increased transmission during low temperatures has been well established. Accordingly, temperature has been suggested to play a role on the viability and transmissibility of SARS-CoV-2, the virus responsible for the COVID-19 pandemic. The receptor binding domain (RBD) of the Spike glycoprotein is known to bind to its host receptor angiotensin-converting enzyme 2 (ACE2) to initiate viral fusion. Using biochemical, biophysical and functional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 87 publications
7
56
0
Order By: Relevance
“…Healthy donors' plasmas, collected before the pandemic, were used as negative controls in flow cytometry and neutralization assays. The conformationally independent S2-specific monoclonal antibody CV3-25 [22,23] was used as a positive control and to normalize Spike expression in our flow cytometry assays, as described [22,24,25]. ACE2 binding was measured using the recombinant ACE2-Fc protein, which is composed of two ACE2 ectodomains linked to the Fc portion of the human IgG [26].…”
Section: Plasmas and Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthy donors' plasmas, collected before the pandemic, were used as negative controls in flow cytometry and neutralization assays. The conformationally independent S2-specific monoclonal antibody CV3-25 [22,23] was used as a positive control and to normalize Spike expression in our flow cytometry assays, as described [22,24,25]. ACE2 binding was measured using the recombinant ACE2-Fc protein, which is composed of two ACE2 ectodomains linked to the Fc portion of the human IgG [26].…”
Section: Plasmas and Antibodiesmentioning
confidence: 99%
“…CV3-25 was used to normalize Spike expression, as reported [24]. The Median Fluorescence intensities (MFI) obtained with ACE2-Fc or plasma Abs were normalized to the MFI obtained with the conformationally and temperature independent CV3-25 anti-S2 antibody [22,23,29] and presented as ratio of the CV3-25-normalized values obtained with the D614G Spike.…”
Section: Cell Surface Staining and Flow Cytometry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that plasma recognition at the surface of infected (N+) cells significantly correlated with the binding of 293T cells expressing the full-length SARS-CoV-2 Spike (Figure 3A,D,G). Similarly, we observed significant correlations with neutralization potency using a well-established pseudoviral assay (Figure 3B,E,H) [4,5,11,18,23,24,33]. Since emerging evidence points to the potential benefits of antibody-mediated effector functions [18][19][20], we also evaluated whether ADCC correlated with recognition of the Spike at the surface of the infected cells.…”
Section: Recognition Of Sars-cov-2 Infected Paecs Correlates With Spike Recognition At the Surface Of 293t Cells Pseudoviral Neutralizatimentioning
confidence: 57%
“…Pre-coupled anti-nucleocapsid (anti-N) antibodies were used to distinguish infected from uninfected bystander cells (Figure 1). Using the conformational independent SARS-CoV-2 S2-specific CV3-25 antibody [18,[23][24][25][26], we detected high levels of the Spike at the surface of the infected N+ cells. CV3-25 specifically bound to infected (N+) pAECs when the cells were infected with the authentic D614G (Figure 1B) or Alpha (B.1.1.7) variant of concern (Figure 1C).…”
Section: Spike Recognition At the Surface Of Infected Primary Human Airway Epithelial Cellsmentioning
confidence: 96%